Food Waste Behaviours at Buffet Restaurants in China. Issue 1 (March 2021) - Wang, Jiayu; Peng, Cheng; Zhang, Meixuan; Zhang, Linfeng; An, Jialin; Yang, Xuewen; Fang, Heyao; Fan, Peiqi; Liu, Miao
Abstract: Food waste is regarded as one of the most challenging issues in the world today with enormous environmental and socio-economic impacts, especially in China, where food waste produced per capita is estimated to be 44 kg per year. However, a review in literature suggests a lack of empirical studies investigating the motivations, management, legislation, policies, and initiative to decrease food waste in the most populated country in the world (with more than 1.4 billion residents). In this study, we collected data through participant observations, casual conversations, and in-depth interviews with 30 Chinese respondents at three buffet restaurants in Haikou, Hainan Province, a popular holiday destination in China. Findings suggest that food waste was significantly influenced by the misperception of the amount of food that a person expected to be able to eat. Food-saving behaviour was also observed as a result of high moral standards and self-discipline. Specifically, people exhibit a higher likelihood of food waste because of value for money. Patrons' lack of environmental knowledge is more likely to contribute to wasteful behaviours. We proposed initiatives to reduce food waste at buffet restaurants in the concluding remarks of this paper.